2013
DOI: 10.1504/ijscm.2013.057557
|View full text |Cite
|
Sign up to set email alerts
|

Cross-culture management: an examination on task, relationship and work overload stress orientations of Japanese and Vietnamese

Abstract: As the world of business has become more globalized than ever, organizational leadership and workforce have also become more culturally diverse. Thus, understanding the leadership behaviors and work-related stress perception of employees in different cultures is strategically important for businesses in the 21 st century. This paper specifically investigated the task and relationship behaviors as well as the work overload stress perception of working adults in Russia and Vietnam. Using Northouse's (2007) Style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…They are acceptable in social science research (Mujtaba and Balboa, 2009;Mujtaba, Afza, and Habib, 2011;Mujtaba and Isomura, 2012;Nguyen, Mujtaba, Tran, and Rujis, 2013;Nguyen, Mujtaba, & Pham, 2013). To determine one's personal leadership characteristics, the respondent circles one of the options that best describe how he or she sees himself or herself (or the person that is being evaluated) regarding each statement.…”
Section: Methodsmentioning
confidence: 99%
“…They are acceptable in social science research (Mujtaba and Balboa, 2009;Mujtaba, Afza, and Habib, 2011;Mujtaba and Isomura, 2012;Nguyen, Mujtaba, Tran, and Rujis, 2013;Nguyen, Mujtaba, & Pham, 2013). To determine one's personal leadership characteristics, the respondent circles one of the options that best describe how he or she sees himself or herself (or the person that is being evaluated) regarding each statement.…”
Section: Methodsmentioning
confidence: 99%
“…Firm performance is enhanced when resources are reconfigured, recombined and reallocated according to the requirements (Hamel & Prahalad, 1990). While appreciating the arguments of (Porter, 2008;Nguyen et al, 2013) who postulated that having operational efficiency alone cannot be argued to constitute a tactic as strategy works in different ways by performing at a cost-effective and profitable fashion. The complexity of the environment has forced firms to include in their strategic plans other dimensions of performance beyond monetary, marketplace and technological considerations (Hamel & Prahalad, 1990), while the studies focused on the resources theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Businesses have unique histories over the route in which particular cultures and norms develop. This customs, norms, attitudes, and traditions may be melded judiciously to form a synergistic work culture where individuals work cooperatively in line with firm goals as employees feel motivated and satisfied (Nguyen, Mujtaba, & Pham, 2013). This argument stresses the essence of culture in performance improvement and strategy operationalization.…”
mentioning
confidence: 99%
“…Many authors found high within-culture agreement with respect to leader attributes and behaviours that are viewed as contributors or impediments to effective leadership and constitute culturally endorsed implicit leadership theories (Adler, 2008; Ambrozheichik, 2011; House et al, 1999; House, Javidan, Hanges & Dorfman, 2002; Nguyen, Ermasova, Demin & Koumbiadis, 2014; Nguyen, Mujtaba, & Pham, 2013; Nguyen, Lam, Ermasova, Geyfman & Mujtaba, 2015; Pradhan & Pradhan, 2016). Irawanto, Ramsey and Ryan (2011, p. 355) discuss ‘the importance of valuing leadership from cross-cultural perspectives by beginning with the transformational leadership.…”
Section: Cross-culture Literaturementioning
confidence: 99%